Pengaruh Total Quality Management terhadap Kinerja Karyawan di PT Bank Pembangunan Daerah Sulawesi Tenggara Cabang Wakatobi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The decline in service quality observed in 2023, such as frequent malfunctions of queue management machines and slow credit processing, indicates that the implementation of Total Quality Management (TQM) at PT Bank Pembangunan Daerah Sulawesi Tenggara, Wakatobi Branch, has not been fully optimized. These issues are particularly evident in aspects of continuous improvement, employee education and training, long-term management commitment, and employee involvement and empowerment. Therefore, this study aims to analyze the effect of Total Quality Management implementation on employee performance at PT BPD Sultra Wakatobi Branch. This research was conducted from February to August 2024 in Wangi-Wangi Regency. The study employed a quantitative research design using a census approach, in which all 40 employees were included as respondents. The data used in this study consisted of primary data collected through questionnaires and secondary data obtained from company documents. Descriptive analysis and Structural Equation Modeling–Partial Least Squares (SEM-PLS) were applied to examine the relationship between TQM and employee performance. The results reveal that long-term management commitment as well as employee involvement and empowerment have a significant effect on employee performance. In contrast, continuous improvement and education and training do not show a significant influence, indicating the need for further evaluation and improvement to strengthen the future implementation of Total Quality Management and enhance organizational performance.